PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP PENURUNAN TINGKAT KECEMASAN MENJELANG UJIAN BLOK PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM AL-AZHAR - Baiq Dara Elok Cintya Monica; Rozikin; Irwan Syuhada; Halia Wanadiatri (Nusantara Hasana Journal, 2023)
Anxiety is a warning mechanism, or a person's physical preparation, when experiencing a threatening or dangerous event. When facing a block exam in medical students anxiety can arise so that it can affect student performance and failure during the block exam. Giving lavender aromatherapy is an alternative treatment that is thought to reduce anxiety levels. Research objective to knowing the effect of giving lavender aromatherapy to reduce anxiety levels before the block exam for students at FK Unizar. This study used a true experimental design with a posttest-only control design. The sampling technique used in this study was purposive sampling. The research was conducted in January 2023. The research was conducted at the Al-Azhar Islamic University Medical Faculty, involving 74 respondents who were divided into two groups: 37 controls and 37 treatments. In the control group (no treatment), with a total of 37 respondents (50.0%) with mild anxiety, in the treatment group (given lavender aromatherapy one day before the test for 15 minutes), with a total of 37 respondents (50.0%), we obtained 4 (5.4%) of respondents who did not experience anxiety, 6 (8.1%) of respondents who experienced mild anxiety, 10 (13.5%) of respondents who experienced moderate anxiety, and 17 (23.9%) of respondents who experienced panic anxiety before the exam. Based on the study level, it was found that from the first to the third year, there was no significant difference (p = 0.93). In the bivariate analysis, obtainedp-value of 0.000 was obtained (p-value < 0.005), with a correlation coefficient of -0.606. There is a significant influence between the effect of giving lavender aromatherapy on reducing anxiety levels before the block exam in Unizar FK students.